2017
DOI: 10.1021/acsmacrolett.7b00204
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Single Catenane on the Solid-State Properties of Mechanically Linked Polymers

Abstract: We report on mechanically linked polymers containing a single catenane in the middle of the chain. These polymers were synthesized by a simple procedure consisting in “clicking” polymer chains onto a functionalized palladium-templated [2]­catenane, allowing the preparation of a variety of mechanically linked polymers. The flexibility of the catenane junction was modulated by removing the Pd ion from the catenane to unlock the macrocycles and increase their mobility. We show that this mobility change has a stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…746 Significant interest in this structure stems from the unique degrees of freedom of the polymer chains, contributing to decreased T g and increased crystallization rate compared to the simple diblock copolymers with covalent junctions. 747 F I G U R E 5 1 Illustration of various cyclic architectures including cyclic-grafted, mechanically linked, and multi-cyclic (fused, bridged, or spiro) topologies [Color figure can be viewed at wileyonlinelibrary.com] F I G U R E 5 2 Synthesis of cyclic-graft polymers via combination of REMP and "graft-to" approach by CuAAC 739,740 Synthetic strategies have also been developed for preparing multicyclic polymer topologies. For example, synthesis of Figure 8-shaped polymers, the simplest form of multicyclic structures, was performed by CuAAC cyclization of clickable chain ends of various precursor templates including 4-arm star polymer, 748 middle-functionalized homopolymer, 749 and BCP (Figure 54), 750 and A 2 B 2 miktoarm star polymer.…”
Section: Complex Cyclic Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…746 Significant interest in this structure stems from the unique degrees of freedom of the polymer chains, contributing to decreased T g and increased crystallization rate compared to the simple diblock copolymers with covalent junctions. 747 F I G U R E 5 1 Illustration of various cyclic architectures including cyclic-grafted, mechanically linked, and multi-cyclic (fused, bridged, or spiro) topologies [Color figure can be viewed at wileyonlinelibrary.com] F I G U R E 5 2 Synthesis of cyclic-graft polymers via combination of REMP and "graft-to" approach by CuAAC 739,740 Synthetic strategies have also been developed for preparing multicyclic polymer topologies. For example, synthesis of Figure 8-shaped polymers, the simplest form of multicyclic structures, was performed by CuAAC cyclization of clickable chain ends of various precursor templates including 4-arm star polymer, 748 middle-functionalized homopolymer, 749 and BCP (Figure 54), 750 and A 2 B 2 miktoarm star polymer.…”
Section: Complex Cyclic Polymersmentioning
confidence: 99%
“…Rotaxanation was performed on a square‐planar Pd(II) complex built from one tridendate and one monodendate ligand, followed by CuAAC conjugation of PMMA and PEO blocks onto the pseudorotaxane in moderate yield 746 . Significant interest in this structure stems from the unique degrees of freedom of the polymer chains, contributing to decreased T g and increased crystallization rate compared to the simple diblock copolymers with covalent junctions 747 …”
Section: Synthesis Of Macromolecules By Coupling Polymeric Building Blocks Using Click Chemistrymentioning
confidence: 99%
“…For example, Fustin 227 has demonstrated that improving the mobility of the component rings of a [2]catenane-by removing the Pd 2+ ion from the crossing point-can result in a decreased glass transition temperature and accelerated crystallization of Furthermore, a polymer gel can be prepared by the thiol-ene reaction between the poly [2]catenane and a crosslinker. Since the IHB can be preserved during gelation, the resulting polymer gel is tough and rigid as a result of the constraining mobility provided by the catenated rings.…”
Section: Applications In Materials Sciencementioning
confidence: 99%
“…Supramolecular chemists have perfectly integrated their expertise in molecular recognition to polymer science and generated numerous supramolecular polymers for various applications . Fabrication of stimuli‐responsive mechanically interlocked supramolecular architectures from macromolecules via host–guest complexation received much attention in recent years . Polypseudorotaxanes and polyrotaxanes are constructed by introducing pseudorotaxane and rotaxane motifs, respectively, in either the main chain or side chain of polymer backbones .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Fabrication of stimuli-responsive mechanically interlocked supramolecular architectures from macromolecules via host-guest complexation received much attention in recent years. [7][8][9][10][11][12][13][14][15][16][17][18] Polypseudorotaxanes and polyrotaxanes are constructed by introducing pseudorotaxane and rotaxane motifs, respectively, in either the main chain or side chain of polymer backbones. 19 Recent advances in polyrotaxanes and polypseudorotaxanes have exposed their proposed applications toward the development of molecular machines, self-healing polymers, responsive materials, and sensors.…”
mentioning
confidence: 99%